PREVALENCE AND IDENTIFICATION OF GASTROINTESTINAL NEMATODES IN DOMESTIC CATS FROM MAKASSAR CITY: PUBLIC HEALTH IMPLICATIONS - Zulfikri Mustakdir; Baso Yusuf; Ahmad Fadhil Ruslan (Buletin Veteriner Udayana, 2025)
Domestic cats (Felis catus) have become increasingly popular companion animals worldwide, yet remain vulnerable to helminth infections with zoonotic potential. This study aimed to identify gastrointestinal nematodes infecting pet cats in Makassar City, Indonesia. Seventy-nine fecal samples were collected from veterinary clinics across Makassar and analyzed using direct smear and flotation techniques. Results revealed a 7.5% (6/79) prevalence of nematode infections, comprising Toxocara sp. (5.1%, 4/79) and Ancylostoma sp. (2.5%, 2/79). Both species pose significant zoonotic risks to human health. These findings underscore the necessity of regular anthelmintic treatment and owner education programs to control parasitic infections in urban pet cats and mitigate public health hazards